Web Services Drive to Decision-Making and Data Consolidation - Lai, Kim Min (2005)
Nowadays, Web is considered as a common tool to share information on the Internet. With the advent of Web Services, many organizations used it as a medium to integrate inter-enterprise application across the Internet. Moreover, Web Services served as distributed peer-to-peer communication between two business entities to overcome middleware limitations. This research aims to study the data distribution Informatics College (multi branch colleges). Apart from this, the purposes of the web Services are to formulate a consolidated and distributed solution (EIS and Mobile Web Services portal prototype) to assists managerial users to do decision-making.